Sustainability communication. Issue 1 (2nd January 2023) - Golob, Urša; Podnar, Klement; Zabkar, Vesna
Abstract: This paper captures both a historical perspective and the current situation of sustainability communication (SC), the relevance and impact of conceptual and empirical contributions, and the future of SC research. By applying the principles of a meta-narrative systematic literature review, we analyze the concepts, theoretical models, and empirical approaches that researchers use in 116 articles in the field. The main manifestations of SC, including sustainability/green advertising, sustainability reporting, and greenwashing, are presented. The analysis reveals a predominant environmental focus on the literature and the dominance of applied communication approaches in SC. We identify several directions that can help advance the field and vision the leading role of the IJA journal in (re)defining and clarifying the concept and integrating the main communication concepts and theories into SC.